Implications of the National Curriculum and Teaching Framework for Early Childhood Care and Education in India - Inder, Alexander; Ramanujan, Fowler (Journal of Research in Vocational Education, 2024)
The Primary objective of the early childhood cove (ECCE) is to achieve positive outcomes in various aspects including optical, physical motor, cognitive, psychoconomic ethical cultural development, as well as early language literacy and numeracy. The NEP 2020 emphasis the significance of universalizing early childhood care and education, aiming to ensure that all students entering grade one are socially prepared by the age of 3 to 6 years. Pre - school education will provide a foundational education to children, preparing them for formal education starting from grade one. The pedagogical & curriculum structure of school education has been modified to reflect the importance of ECCE. The NCERT has been looked with creating a national curriculum and pedagogical frame work for childhood care & education in the creation to children up to the age of 8 Pre kinder garden classes are being discussed as a transitional program b/w early childhood & primary school. The policy aim to provide certification programs from ECCE to primary school with a focus on digital access to early childhood education.